Carnitine and γ‐Butyrobetaine Stimulate Elimination of Meldonium due to Competition for OCTN2‐mediated Transport. Issue 5 (10th January 2017) - Liepinsh, Edgars; Makarova, Elina; Sevostjanovs, Eduards; Hartmane, Dace; Cirule, Helena; Zharkova‐Malkova, Olga; Grinberga, Solveiga; Dambrova, Maija
Abstract: Meldonium (3‐(2, 2, 2‐trimethylhydrazinium)propionate) is the most potent clinically used inhibitor of organic cation transporter 2 (OCTN2). Inhibition of OCTN2 leads to a decrease in carnitine and acylcarnitine contents in tissues and energy metabolism optimization‐related cardioprotective effects. The recent inclusion of meldonium in the World Anti‐Doping Agency List of Prohibited Substances and Methods has raised questions about the pharmacokinetics of meldonium and its unusually long elimination time. Therefore, in this study, the rate of meldonium washout after the end of the treatment was tested with and without administration of carnitine, γ‐butyrobetaine (GBB) and furosemide to evaluate the importance of competition for OCTN2 transport in mice. Here, we show that carnitine and GBB administration during the washout period effectively stimulated the elimination of meldonium. GBB induced a more pronounced effect on meldonium elimination than carnitine due to the higher affinity of GBB for OCTN2. The diuretic effect of furosemide did not significantly affect the elimination of meldonium, carnitine and GBB. In conclusion, the competition of meldonium, carnitine and GBB for OCTN2‐mediated transport determines the pharmacokinetic properties of meldonium. Thus, due to their affinity for OCTN2, GBB and carnitine but not furosemide stimulated meldonium elimination. During long‐term treatment, OCTN2‐mediated transport ensures a high muscle content of meldonium, while tissue clearance depends on relatively slow diffusion, thus resulting in the unusually long complete elimination period of meldonium.